IMPACT OF THE NEW FACET LEADERSHIP STYLE ON JOB SATISFACTION IN THE SECONDARY SCHOOLS OF MAURITIUS - Subrun, Veerunjaysingh; Subrun, Leena (INTI International University, 2022)
With the advent of globalization, competition in the education system has been in the limelight. Successive governments have been investing massively in education. The utilization of the appropriate leadership styles and their impact on job satisfaction in managing the different types of arising circumstances have turned out to be of utmost importance in the impartation of quality education and educational attainment. Leadership styles of the school leaders and job satisfaction are responsible for the sustainability and future of all institutions. The aim of the study is to understand the impact of educational leadership styles in terms of the New Facet Leadership style on job satisfaction in the Mauritian education system. Data have been gathered from five hundred actors of the education system in the private and state secondary schools of Mauritius. It analyses the impact of the various socio-psychological in relation to the New Facet Leadership Style, work culture, the attitude of the members towards their job, occupational self-efficacy and self-concept on job satisfaction in the non-profit-making state and private secondary schools in Mauritius through the SPSS and The SPSS AMOS. As the main confirmatory tool, the Structural Equation Modeling has been used to gauge the impact of the New Facet Leadership Style (composed of Contingency leadership, Managerial Leadership, Participative leadership, Instructional Leadership and Moral leadership, along with the transformational leadership style) based on the contingency and transformational leadership theories practised by the leaders positively affect the job satisfaction. The present study establishes levels for other scholars to further investigate the concept of job satisfaction and the leadership styles in terms of the New Facet Leadership Style at the National and International levels using Structural Equation Modeling as the main tool of analysis.